A meta-analytic comparison of the effects of consuming carbohydrate with and without protein on postexercise plasma insulin and glucagon responses in healthy, trained males - Kuo, T.-Y.; Barnes, J.; Laurson, K.; Russell, L. (Scientific Journal of Sport and Performance, 2023)
This meta-analysis evaluates how hydrolysed protein and carbohydrate (CHO) mixtures compare with intact protein and CHO mixtures regarding post-exercise plasma insulin and glucagon responses in healthy endurance trained males. Studies measuring insulin and/or glucagon following an exercise bout with ingestion of CHO vs. CHO+ protein were included. Random-effects meta-analyses were conducted on the insulin peaks over time. Overall, 33 trials from 20 articles were included. The ingestion of CHO+ protein induced significantly higher insulin peaks than ingestion of CHO only from 30 to 240 minutes postexercise (30-180 min: p < .001, 210-240 min: p < .01), higher insulin area under the curve (p < .001), and greater muscle FSR (p < .001). No statistically significant differences on insulin peaks over time were found between the ingestion of CHO+ intact protein and CHO+ hydrolysed protein or differences in muscle glycogen synthesis rate or glycogen peaks. Findings provide evidence the co-ingestion of CHO+ protein is a better strategy for recovery for endurance-type male athletes than the ingestion of CHO only. However, more research is warranted to understand whether there are differences between the ingestion of intact protein and its hydrolysed counterpart with CHO, and the impact on glucagon responses.